Dried Persimmon Fruit: A Year-round Available Product - Ali Sarkhosh; Fariborz Habibi; Muhammad A. Shahid; Steven A. Sargent; Jeffrey K. Brecht (EDIS, 2024)
Persimmons (Diospyros kaki) are known for their sweet and flavorful taste. They are native to Asia, specifically China, and were first grown in Florida in the 1870s. Persimmons are still not as popular in the United States as other fruits, but interest has been growing in recent years. Persimmon fruit are generally classified into astringent and non-astringent types. Astringent varieties can have adverse health effects caused by tannins and must be fully ripe (soft) or artificially treated to remove astringency. Drying is a common method to preserve and extend the shelf life of persimmons while also enhancing the flavor, color, and nutritional value of persimmons. There are different methods to dry persimmons, including traditional and modern methods.